Pengaruh Pandemi COVID-19 Terhadap Kinerja Keuangan Perbankan - Ais Robiatul Adawiyah (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
This research was conducted to analyze are differences in conventional banks quarter II before and during the pandemi COVID-19 based on the total asset turnover ratio, NPM ratio, LDR ratio, and ROE ratio. This research uses descriptive quantitative methods by a comparative approach, because the data used was numbers and analyzed using statistic. This research is of a comparing two or more of the properties and objects that are scruntinized in a particular framework of thought. This research uses the quarterly II 2019-2021 finance report data. The research population was taken from a registered private bank in OJK (Otoritas Jasa Keuangan). Statistical methods used are descriptive and paired t-test. This research shows that (1) total asset turnover have no difference fiinancial performance before and during pandemi COVID-19. (2) NPM have difference financial performance before and during pandemi COVID-19. (3) LDR have no difference financial performance before and during pandemi COVID-19. (4) ROE have difference financial performance before and during pandemi COVID-19